2018
DOI: 10.1111/nep.13214
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating barriers to immunosuppressant medication adherence in renal transplant patients

Abstract: Over half the patients self-reported non-adherence. The main modifiable barriers leading to non-adherence were forgetfulness and skipped doses. Personalised interventions focused on habit forming may improve adherence in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
(104 reference statements)
7
35
0
2
Order By: Relevance
“…As other reports also have shown , the majority of these NoAd patients took all the prescribed doses but had a time deviation (22%). A 2‐h time deviation as the BAASIS © form defines as nonadherence may seem rigid and its clinical relevance in RTxR has been questioned . Recent pharmacokinetic simulation data indicate that ±4 h may be more relevant .…”
Section: Discussionmentioning
confidence: 99%
“…As other reports also have shown , the majority of these NoAd patients took all the prescribed doses but had a time deviation (22%). A 2‐h time deviation as the BAASIS © form defines as nonadherence may seem rigid and its clinical relevance in RTxR has been questioned . Recent pharmacokinetic simulation data indicate that ±4 h may be more relevant .…”
Section: Discussionmentioning
confidence: 99%
“…RTX patients reported higher necessity of medicines than while in dialysis. The Necessity‐concern differential, which is found to be correlated with adherence, increased markedly. One reason for this increase may be that the patients are thoroughly informed and trained about the use and necessity of immunosuppressants after RTX.…”
Section: Discussionmentioning
confidence: 97%
“…Depressive symptoms were associated with high scores in the subscales Harm, Overuse, and Concern. Some studies have found that depression may be linked to a low Necessity‐concern differential, meaning that the patients’ concerns about their medications surpass the expected necessity of them . The same studies showed that this may be an important barrier to adherence, while others have not found similar associations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations